CHARACTERISTICS AND DISTINCTIONS OF ISLAMIC EDUCATION IN ACTUAL, FACTUAL AND PLURALIST ISLAMIC DISCOURSE - Lalu Gede Muhammad Zainuddin Astani; Prosmala Hadisaputra; Muh. Zulkifli (An-Nahdlah: Jurnal Pendidikan Islam, 2023)
This article discusses the features and characteristics of Islamic education in actual, factual, and pluralist Islamic discourse. This article includes a literature review, where the initial investigation was carried out through searching on Google and Google Scholar. The author has not found articles that comprehensively discuss actual, factual, and pluralist Islam in the search process. This article aims to answer one problem formulation, namely how the concept of Islam is actual, factual, and plural in the context of Islamic education. The results of the analysis show that 1) actual Islamic education can be understood as contextual, contemporary, and heretical education. Its distinction is Islamic education based on trending, urgent, and futuristic topics; 2) Factual Islamic education is Islamic education based on facts, reality, and the necessity of a nation that lives in diversity. The distinction is that Islamic education is based on reality or necessity and based on truth. Inevitability can be seen from the geographical location, religion, ethnicity, customs, language, social and culture. Truth-based means that Islamic education is practised based on a scientific process; 3) Pluralist Islamic education, namely education, accommodates multicultural values, peace, inclusiveness, and deradicalisation.